ALOHA From the Edge: Reconciling Three Decades of in Situ Eulerian Observations and Geographic Variability in the North Pacific Subtropical Gyre - Kavanaugh, Maria T.; Church, Matthew J.; Davis, Curtiss O.; Karl, David M.; Letelier, Ricardo M.; Doney, Scott C. (Frontiers in Marine Science, 2018)
Global analyses of satellite and modeled data suggest decreased phytoplankton abundance and primary productivity in oligotrophic gyres as they expand in response to increased surface temperatures, shoaling of surface mixed layers, and decreased supply of subsurface macronutrients. However, analogous changes in the phytoplankton have not been evident in situ at Hawaii Ocean Time-series (HOT) Station ALOHA (22°45′N, 158°00′W), suggesting that physiological or structural reorganization not observed from space, uncorrected sensor drift, or uncharacterized geographic variability may be responsible for the apparent discrepancy. To address the latter, we compared interannual patterns of in situ phytoplankton dynamics and mixed layer properties to gyre extent and boundary location based on multiple definitions including dynamic topography, a threshold of satellite surface chlorophyll (chl a) ≤0.07 mg m−3, and multivariate biophysical seascapes using modeled or satellite data. Secular increases in gyre extent were apparent, although the rate of expansion was much slower than previously reported, whereas strong interannual oscillations were evident for all definitions of the gyre. Modeled and satellite-based multivariate seascapes agreed well in terms of expansion (surface area of seascapes) and isolation of Station ALOHA (distance to seascape boundary) resulting in a combined data record of nearly three decades. Isolation was associated positively with the North Pacific Gyre Oscillation (NPGO), and negatively with Multivariate ENSO Index (MEI), and Pacific Decadal Oscillation (PDO). The converse was true for the gyre's expansion. Expansion followed a shoaling and freshening of the surface mixed layer and declines of in situ net primary production (PP) suggesting that Station ALOHA may serve as an early indicator of gyre biogeographic patterns. Lags between geographic indicators and in situ conditions appear to partially explain past observed discrepancies between patterns from satellite remote sensing and those from in situ conditions at Station ALOHA.